Higher Order Oligomerization of the Licensing ORC4 Protein Is Required for Polar Body Extrusion in Murine Meiosis. Issue 9 (3rd May 2017) - Nguyen, Hieu; James, Nicholas G.; Nguyen, Lynn; Nguyen, Thien P.; Vuong, Cindy; Ortega, Michael A.; Jameson, David M.; Ward, W. Steven
ABSTRACT: We have previously shown that the DNA replication licensing factor ORC4 forms a cage around the chromosomes that are extruded in both polar bodies during murine oogenesis, but not around the chromosomes that are retained in the oocyte or around the sperm chromatin. We termed this structure the ORC4 cage. Here, we tested whether the formation of the ORC4 cage is necessary for polar body extrusion (PBE). We first experimentally forced oocytes to extrude sperm chromatin as a pseudo‐polar body and found that under these conditions the sperm chromatin did become enclosed in an ORC4 cage. Next, we attempted to prevent the formation of the ORC4 cage by injecting peptides that contained sequences of different domains of the ORC4 protein into metaphase II (MII) oocytes just before the cage normally forms. Our rationale was that the ORC4 peptides would block protein‐protein interactions required for cage formation. Two out of six tested peptides prevented the ORC4 cage formation and simultaneously inhibited PBE, resulting in the formation of two pronuclei (2 PN) that were retained in the oocyte. Together, these data demonstrate that ORC4 oligomerization is required to form the ORC4 cage and that it is required for PBE. J. Cell. Biochem. 118: 2941–2949, 2017. © 2017 Wiley Periodicals, Inc. Abstract : The DNA licensing protein ORC4 forms a cage around the chromosomes that will be extruded in the polar body during oogenesis and fertilization. We disrupted this cage and showed that it is required for polar body extrusion.